Selective sodium halide over potassium halide binding and extraction by a heteroditopic halogen bonding [2]catenane † - Tay, HM; Docker, A; Hua, C; Beer, PD (Royal Society of Chemistry, 2024)
The synthesis and ion-pair binding properties of a heteroditopic [2]catenane receptor exhibiting highly potent and selective recognition of sodium halide salts are described. The receptor design consists of a bidentate halogen bonding donor motif for anion binding, as well as a di(ethylene glycol)-derived cation binding pocket which dramatically enhances metal cation affinity over previously reported homo[2]catenane analogues. 1H NMR cation, anion and ion-pair binding studies reveal significant positive cooperativity between the cation and anion binding events in which cation pre-complexation to the catenane subsequently ‘switches-on’ anion binding. Notably, the heteroditopic catenane displayed impressive selectivity for sodium halide recognition over the corresponding potassium halides. We further demonstrate that the catenane is capable of extracting solid alkali metal salts into organic media. Crucially, the observed solution phase binding selectivity for sodium halides translates to superior functional extraction capabilities of these salts relative to potassium halides, overcoming the comparatively higher lattice enthalpies NaX > KX dictated by the smaller alkali metal sodium cation. This is further exemplified in competitive solid–liquid experiments which revealed the exclusive extraction of sodium halide salts from solid mixtures of sodium and potassium halide salts.